Detection of Rotational Acceleration of Bennu Using HST Light Curve Observations. Issue 4 (15th February 2019) - Nolan, M. C.; Howell, E. S.; Scheeres, D. J.; McMahon, J. W.; Golubov, O.; Hergenrother, C. W.; Emery, J. P.; Noll, K. S.; Chesley, S. R.; Lauretta, D. S.
Abstract: We observed the near‐Earth asteroid (101955) Bennu from the ground in 1999 and 2005, and with the Hubble Space Telescope (HST) in 2012, to constrain its rotation rate. The data reveal an acceleration of 2.64  ±  1.05 × 10 −6  deg/day 2, which could be due to a change in the moment of inertia of Bennu or to spin up from the Yarkovsky‐O'Keefe‐Radzievskii‐Paddack effect or other source of angular momentum. The best solution is within 1 σ of the period determined by Nolan et al. (2013, https://doi.org/10.1016/j.icarus.2013.05.028 ). The Origins, Spectral Interpretation, Resource Identification, and Security–Regolith Explorer (OSIRIS‐REx) mission will determine the rotation state independently in 2019. Those measurements should show whether the change in rotation rate is a steady increase (due, e.g., to the Yarkovsky‐O'Keefe‐Radzievskii‐Paddack effect) or some other phenomenon. The precise shape and surface properties measured by the OSIRIS‐REx science team will allow for a better understanding of variations in rotation rate of small asteroids. Plain Language Summary: We observed near‐Earth asteroid (101955) Bennu—the target of the Origins, Spectral Interpretation, Resource Identification, and Security–Regolith Explorer (OSIRIS‐REx) spacecraft mission—using ground‐based telescopes and the Hubble Space Telescope. Our measurements show that its rotation has been speeding up since 1999. This change could be due to a change in the shape of Bennu or to the Yarkovsky‐O'Keefe‐Radzievskii‐Paddack effect: As the sunlight received by an asteroid is reflected or radiated back to space, the change in direction of the light coming in and going out pushes on the asteroid and can cause it to spin faster or slower, depending on its shape and orientation. The specific properties of the surface, such as the position of boulders, can have a large influence on the outcome. In the next few years, the OSIRIS‐REx team will study Bennu and independently measure its rotation, helping us to better understand the structure and dynamical evolution of small asteroids. Key Points: Asteroid (101955) Bennu has been rotating faster over time since 1999 An acceleration in its rotation rate is needed to fit all the photometric measurements of asteroid Bennu The measured acceleration of Bennu is consistent with theoretical calculations of the total effects of the YORP effect